1984
DOI: 10.2466/pms.1984.58.2.339
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Pain Experience, and Pain Report: A Signal-Detection Study

Abstract: The effect of experimentally induced anxiety on pain perception was examined using a signal detection discrimination experiment. The experimental condition consisted in unsignalled application of very painful stimuli which substantially raised state anxiety. The discrimination task included the total range of painful stimuli. The results indicated a range-specific effect of anxiety on pain, particularly on increased sensitivity in the upper range of intensities. The importance of testing the effect of anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…For example, anxiety levels have been shown to predict pain severity and pain behavior in acute and chronic pain patients (Kain et al, 2000;van den Hout et al, 2001), and anxiety reduction techniques and anxiolytic drugs have been reported to be successful in ameliorating pain associated with medical procedures (Suls and Wan, 1989;Dellemijn and Fields, 1994). Experimental studies have confirmed the enhancing effect of anxiety on pain for different components and measures of pain, e.g., ratings of pain intensity (Al Absi and Rokke, 1991) and unpleasantness (Weisenberg et al, 1984), pain threshold (Rhudy and Meagher, 2000), and pain discrimination (Schumacher and Velden, 1984). Anxiolytic drugs reverse the experimental effect (Gracely et al, 1978;Janssen and Arntz, 1999).…”
Section: Abstract: Hyperalgesia; Hippocampus; Classical Fear Conditimentioning
confidence: 99%
“…For example, anxiety levels have been shown to predict pain severity and pain behavior in acute and chronic pain patients (Kain et al, 2000;van den Hout et al, 2001), and anxiety reduction techniques and anxiolytic drugs have been reported to be successful in ameliorating pain associated with medical procedures (Suls and Wan, 1989;Dellemijn and Fields, 1994). Experimental studies have confirmed the enhancing effect of anxiety on pain for different components and measures of pain, e.g., ratings of pain intensity (Al Absi and Rokke, 1991) and unpleasantness (Weisenberg et al, 1984), pain threshold (Rhudy and Meagher, 2000), and pain discrimination (Schumacher and Velden, 1984). Anxiolytic drugs reverse the experimental effect (Gracely et al, 1978;Janssen and Arntz, 1999).…”
Section: Abstract: Hyperalgesia; Hippocampus; Classical Fear Conditimentioning
confidence: 99%
“…Negative emotions with low-to-moderate intensity/arousal (e.g., anxiety) lead to enhanced pain/nociception (e.g., Haslam, 1966;Rhudy and Meagher, 2000;Schumacher and Velden, 1984;Weisenberg et al, 1984), whereas negative emotions with high intensity/arousal (e.g., fear, intense stress) lead to decreased pain/nociception (e.g., Janssen and Arntz, 2001;Pitman et al, 1990;Rhudy and Meagher, 2000, 2001bRhudy et al, 2004). Although arousal was manipulated in the present study, pictures would not be expected to inhibit pain/ nociception because unpleasant pictures do not represent a threat significant enough to evoke intense negative emotions in healthy participants.…”
Section: Relations To Previous Studies Of Emotion and Pain/nociceptionmentioning
confidence: 99%
“…Preclinical investigations have confirmed the enhancing effect of anxiety on nociception for different components and measures, including nociception intensity (Al Absi and Rokke, 1991), nociception threshold (Rhudy and Meagher, 2000), and nociception discrimination (Schumacher and Velden, 1984). Also, in clinical settings, it has been shown that anxiety levels predict pain severity and pain behavior in acute and chronic pain patients (Kain et al, 2000;Van Den Hout et al, 2001), while anxiety reduction techniques and anxiolytic drugs are successful in ameliorating medical procedure associated pain (Suls and Wan, 1989;Dellemijn and Fields, 1994).…”
Section: Introductionmentioning
confidence: 95%